Peran Program Apotik Hidup Dalam Meningkatkan Kesadaran Lingkungan Siswa SD Negeri 1 Padokan - Rahmawan Candra Mualim; Rusli Dedi Mustofa; Anggi Ariyanto; Hermawan Wahyu Setiadi (Yayasan Al-Afif, 2025)
This study aims to examine the role of a school-based medicinal plant garden program in enhancing environmental awareness among students at SD Negeri 1 Padokan by exploring their experiences, meanings, and shifts in ecological attitudes and behaviors. A qualitative case study design was employed, utilizing in-depth interviews, participatory observations, and documentation involving students, teachers, and garden-based learning activities. Thematic analysis revealed four key findings: strengthened ecological awareness, enriched contextual nature-based learning, increased learning motivation and interest, and the development of collaboration and social responsibility. These results indicate that direct engagement in cultivating medicinal plants contributes to the reinforcement of eco-literacy and the internalization of pro-environmental behavior. The study highlights the relevance of medicinal plant gardens as an effective environmental education strategy for primary schools and recommends further research on the long-term impacts of such programs within students’ homes and communities.